Long‐term impact of diabetes in patients with ST‐segment elevation myocardial infarction: Insights from the EXAMINATION randomized trial. Issue 7 (20th March 2019) - Jimenez‐Quevedo, Pilar; Brugaletta, Salvatore; Cequier, Angel; Iñiguez, Andrés; Serra, Antonio; Mainar, Vicente; Campo, Gianluca; Tespili, Maurizio; Nombela‐Franco, Luis; del Trigo, Maria; Gonzalo, Nieves; Escaned, Javier; et al.
Abstract: Background: Long‐term outcomes of diabetic patients suffering from ST‐segment elevation myocardial infarction (STEMI) and treated with second‐generation drug‐eluting stent have been scarcely evaluated. The aim of this posthoc subanalysis of the EXAMINATION trial was to compare 5‐year outcomes according to the presence of diabetes mellitus. Methods: From a total of 1, 497 patients included in the trial, 258 were diabetics ( n = 137, received everolimus‐eluting stent (EES) and n = 121 bare‐metal stent (BMS); whereas 1, 239 were nondiabetics ( n = 613 treated with EES and n = 626 with BMS). Patient‐oriented combined endpoint (POCE) defined as all‐cause death, any MI or any revascularization, and other clinical parameters were collected up to 5‐years. All results were adjusted for various potential confounders. Results: At 5‐years, patients with diabetes showed similar rates of POCE between diabetics treated with EES and those treated with BMS (32.8% vs. 32.2%; p  = 0.88). However, rates of TLR were significantly lower in the EES group (4.4% vs. 9.9%; HR 0.52 (0.29–0.94); P = 0.03). In non‐diabetics, the use of EES was associated with a significant improvement in all‐clinical parameters except for MI rate: POCE: [10.0% vs. 12.6%; HR 0.78(0.62–0.98); P = 0.038], all cause death: [7.0% vs. 12.1%; HR 0.62(0.42–0.90); P = 0.014], and [TLR: 4.2 vs. 6.7; HR 0.60 (0.37–0.98); P = 0.04]. Overall, diabetics showed higher rate of POCE at 5‐years (32.6% vs. 21.5% in nondiabetics HR1.45[1.03–2.04];p = 0.03) driven by increased rates of MI and the need for revascularization that occurred in coronary segments remote from target lesions [2.7% vs. 1.1%; HR: 2.27 (1.12–5.23); P = 0.02 and 14% vs. 6.2%; HR: 2.11 (1.38–3.22); P = 0.001, respectively]. Conclusions: Diabetics had worse clinical outcomes than nondiabetics after STEMI mainly due to atherosclerosis progression. At 5‐years, the treatment with EES did not reduce the rate of POCE in diabetics but reduced the need for revascularization compared with BMS.